Study on the Phenolic Content, Antioxidant and Antimicrobial Effects of Sternbergia clusiana - Mammadov, R.; Kara, Y.; Ertem Vaizogullar, H. (Asian Journal of Chemistry, 2011)
In this study, the antioxidant, antimicrobial effects and phenolic content of Sternbergia clusiana were investigated. Antimicrobial activity was determined by agar-well diffusion method. The total phenolic content of extracts was determined using to the Folin-Ciocalteu method. Total antioxidant activity was evaluated by β-carotene-linoleic acid method. The highest phenolic content was found in bulb-methanol extract. Results showed that the highest antioxidant activity was in the bulb-ethanol solution and the least antioxidant activity was in the bulb-benzene solution. According to free radical scavenging, the values of bulb-methanol, bulb-benzene and leaf-acetone were found to be higher than the values of butylated hydroxytoluene (BHT). Sternbergia bulb ethanol (SBE), sternbergia bulb acetone (SBA), sternbergia leaf ethanol (SLE) and sternbergia bulb benzene (SBB) extracts have showed mostly effect on G(+) bacteria. Sternbergia bulb ethanol and sternbergia bulb acetone extracts have showed mostly effect on G(–) bacteria. Extracts of S. clusiana are quite effective on Candida albicans ATCC 10239 except for sternbergia leaf methanol (SLM ). In this study, extracts of S. clusiana have showed antioxidant and antimicrobial activity.